PENILAIAN POTENSI DAYA TARIK WISATA ALAM RIAM PALAYO DESA CIPTA KARYA KECAMATAN SUNGAI BETUNG KABUPATEN BENGKAYANG - Meriyana, Meriyana; Siahaan, Sarma; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2025)
Riam Palayo is mostly known to the people of Bengkayang Regency, but there has been no study assessing the potential of the Riam's tourist attraction. The aim of the research is to obtain the potential value of natural tourist attractions. The method used is a survey method with observation and interview techniques using a questionnaire. The sample was taken as many as 66 respondents using accidental sampling and purposive sampling techniques. Data processing uses the data scoring method in accordance with the 2003 Natural Tourism Objects and Attractions (ODTWA PHKA) guidelines. The results of the assessment of Riam Palayo's natural tourism potential consist of Tourist Attraction (B), Accessibility (B), Socio-Economic Conditions (A), Accommodation (A), Visitor Facilities and Infrastructure (A), Availability of Clean Water (A). The ODTWA Alam Riam Palayo calculation results obtained a score of 561.29, meaning that it has enough potential to be developed as a natural tourist attraction, but it still needs to improve accessibility and maintain the existence of the attraction. Keyword: Cipta Karya Village, Riam Palayo, Tourist Attraction, Tourism Potential Abstrak Riam Palayo sebagian besar dikenal masyarakat Kabupaten Bengkayang namun belum ada kajian penilaian potensi daya tarik wisata Riam tersebut. Tujuan penelitian adalah untuk mendapatkan nilai potensi daya tarik wisata alam. Metode yang digunakan adalah metode survei dengan teknik observasi dan wawancara menggunakan kuesioner. Pengambilan sampel sebanyak 66 responden menggunakan teknik Accidental sampling dan Purvosive sampling . Pengolahan data menggunakan metode Skoring data sesuai pedomana Objek dan Daya Tarik Wisata Alam (ODTWA PHKA) tahun 2003. Hasil penilaian potensi wisata alam Riam Palayo terdiri dari Daya Tarik Wisata (B), Aksesibilitas (B), Kondisi Sosial Ekonomi (A), Akomodasi (A), Sarana dan Prasarana Pengunjung (A), Ketersediaan Air Bersih (A). Hasil perhitungan ODTWA Alam Riam Palayo diproleh skor 561,29, artinya cukup potensial untuk dikembangkan sebagai objek wisata alam, namun masih perlu peningkatan perbaikan aksessibilitas dan mempertahankan keberadaan daya tarik . Kata kunci: Desa Cipta Karya, Riam Palayo, Daya Tarik Wisata, Potensi Wisata